An expansion of phenotype: novel homozygous variant in the MED17 identified in patients with progressive microcephaly and global developmental delay. (2nd October 2022) - Rafiullah, Rafiullah; Albalawi, Alia M.; Alaradi, Sultan R.; Alluqmani, Majed; Mushtaq, Muhammad; Wali, Abdul; Basit, Sulman
Abstract: Global developmental delay (GDD) is a lifelong disability that affects 1–3% of the population around the globe. It is phenotypically variable and highly heterogeneous in terms of the underlying genetics. Patients with GDD are intellectually disabled (ID) manifesting cognitive impairment and deficient adaptive behavior. Here, we investigated a two-looped consanguineous family segregating severe ID, seizure, and progressive microcephaly. Magnetic resonance imaging (MRI) of the brain showed mild brain atrophy and myelination defect. Whole exome sequencing (WES) was performed on the DNA samples of two patients and a novel homozygous missense variant (Chr11:g0.93528085; NM_004268.5_c.871T > C; p. Trp291Gly) was identified in the MED17 gene. Sanger sequencing revealed that the identified variant is heterozygous in both parents and healthy siblings. This variant is conserved among different species, causes a non-conserved amino acid change, and is predicted deleterious by various in silico tools. The variant is not reported in population variant databases. MED17 (OMIM: 613668) encodes for the mediator of RNA polymerase II transcription complex subunit 17. Structure modeling of MED17 protein revealed that Trp291 is involved in different inter-helical interactions, providing structural stability. Replacement of Trp291Gly, a less hydrophobic amino acid loses the inter-helical interaction leading to a perturb variant of MED17 protein.